2022
DOI: 10.4103/aja2021102
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for successful sperm retrieval by microdissection testicular sperm extraction in men with nonobstructive azoospermia and a history of cryptorchidism

Abstract: This study aims to explore the factors influencing the success rate of the microdissection testicular sperm extraction (Micro-TESE) in patients with nonobstructive azoospermia (NOA) and cryptorchidism. Clinical data of 162 patients with cryptorchidism who underwent Micro-TESE due to infertility from December 2015 to May 2020 in the First Affiliated Hospital of Nanjing Medical University were analyzed retrospectively. In the univariate analysis, significant differences in the age of patient at the time of orchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…1 a, the maximum and minimum values of Age (91 and 36) were collapsed to 100 and 0, respectively; HL and NHL in Pathology corresponded to 61 and 65, respectively; the presence or absence of Systemic therapy corresponded to 51 and 61, respectively; Localized/Regional and Distant in SEER Stage corresponded to 55 and 61, respectively; the presence or absence of Surgery corresponded to 61 and 52, respectively; Female and Male corresponded to 61 and 70, respectively; MCA and Poverty corresponded to 61 and 82, respectively; Unilateral and Bilateral corresponded to 61 and 75, respectively. The method of nomograms is based on the score corresponding to each predictor of a patient, summed to calculate the total score, and the risk value corresponding to the score of the total points is the probability of an event for a patient (dead for OS, dead from PAL for DSS and FGS) 16 . A patient with ID 50031326 is used as an example.…”
Section: Resultsmentioning
confidence: 99%
“…1 a, the maximum and minimum values of Age (91 and 36) were collapsed to 100 and 0, respectively; HL and NHL in Pathology corresponded to 61 and 65, respectively; the presence or absence of Systemic therapy corresponded to 51 and 61, respectively; Localized/Regional and Distant in SEER Stage corresponded to 55 and 61, respectively; the presence or absence of Surgery corresponded to 61 and 52, respectively; Female and Male corresponded to 61 and 70, respectively; MCA and Poverty corresponded to 61 and 82, respectively; Unilateral and Bilateral corresponded to 61 and 75, respectively. The method of nomograms is based on the score corresponding to each predictor of a patient, summed to calculate the total score, and the risk value corresponding to the score of the total points is the probability of an event for a patient (dead for OS, dead from PAL for DSS and FGS) 16 . A patient with ID 50031326 is used as an example.…”
Section: Resultsmentioning
confidence: 99%
“…There were several studies exploring the influencing factors of successful sperm retrieval, including a unilateral or bilateral cryptorchidism history, age at orchidopexy, testicular volume, and serum sexual hormone levels, while many views were controversial [ 29 32 ]. The logistics regression and ROC curve analyzes showed that orchidopexy age was a significant predictor to retrieve sperm, even though the predictive utility was not perfect enough probably due to an inadequate sample size.…”
Section: Discussionmentioning
confidence: 99%
“…By mapping the value of each factor to the "points" axis, the points for early death probability for each variable were obtained. The total points can be calculated by summing them up [ 15 ].…”
Section: Methodsmentioning
confidence: 99%